EFEKTIVITAS PENERAPAN TEORI BRUNER PADA MATERI MENGHITUNG LUAS PERSEGI DAN PERSEGI PANJANG KELAS III SD - Khairunnisa, Nuriah; Bistari, Bistari; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract The research method used was non-actual experiments (pre-experimental design) the research design used in this research was one shot case study. The subjects of this research are 3rd grade student on 3A students of the SDN 06 Pontianak Kota, amount of students were involved in this research was 20 student. results of the study shows that the ability of teaching (researchers) in the implementation of learning by applying the Bruner Theory is quite good with an average of 3.39 and the percentage of student learning activities classified as active with an average of 78.99%. Student learning outcomes are said to be classically complete if in class there are at least 75% of students who score more than or equal to KKM which is 75. However, completeness of classical learning outcomes obtained by students in this study is only 65%. In this case it means that students have not yet reached the besf result of classical learning outcomes. Learning process were effective if it approach the minimum criteria of three aspects, among them are the ability of teachers in implementing learning, student learning activities, and student learning outcomes. Because there is one indicator of effectiveness that is not achieved, so it can concluded that learning by applying the Bruner Theory to the material calculating the area of a square and rectangle, is not effectively used in 3rd A grade of SDN 06 Pontianak kota .Keywords: Learning Effectiveness, Application of Bruner's Theory, CalculatingSquare and Rectangular Areas.